Chinese herbal products and the reduction of risk of breast cancer among females with type 2 diabetes in Taiwan: A case–control study - Wu, Chien-Tung (Medicine (Baltimore), 2018)
Women with type 2 diabetes have a higher risk of developing breast cancer. In Taiwan, traditional Chinese medicine is widely used to treat diabetes; however, its precise influence has not been empirically tested. The objective of the case–control study is to estimate the effect on the risk of breast cancer of using traditional Chinese medicine for women with type 2 diabetes. More than 80% of women with type 2 diabetes have used traditional Chinese medicine. The most commonly prescribed drug was metformin and the herbal formulas were the Di Huang Wan series, including Liu Wei Di Huang Wan, Qi Ju Di Huang Wan, and Zhi Bai Di Huang Wan, followed by Bai Hu Jia Ren Shen Tang and Yu Quan Wan. For the effect of metformin, women who used traditional Chinese medicine including Di Huang series have a lower risk of breast cancer HR: 0.35 (95%CI: 0.23–0.51) in women younger than 55 and HR: 0.54 (95%CI: 0.37–0.79) in women older than 55. The protective effect of the Di Huang Wan series may be due to the synergetic effect of reducing blood glucose or increasing insulin sensitivity and delaying the insulin resistance of cells. The relationship between the Di Huang Wan series and breast cancer of women with type 2 diabetes requires further investigation.